1982
DOI: 10.1152/jn.1982.47.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of cutaneous mechanoreceptors recorded in mandibular division of Gasserian ganglion of the rabbit during movements of lower jaw

Abstract: 1. The activity of cutaneous mechanoreceptors was recorded extracellularly in the mandibular division of the Gasserian ganglion of hemidecerebrate anesthetized rabbits. Fifty-four hair follicle afferents and 80 skin mechanoreceptor afferents were functionally identified. Their receptive-field characteristics were described and their activity patterns were recorded while the jaw was displaced by hand in the vertical, horizontal, and anterior-posterior directions, and during masticatory movements. 2. All hair fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Although the primary afferents of both submodalities are excellent tactile event detectors, coded with bursts in the mossy fibers (7,18), they also function as proprioceptors, and then as rate-coding estimators operating at lower firing frequencies (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Although the primary afferents of both submodalities are excellent tactile event detectors, coded with bursts in the mossy fibers (7,18), they also function as proprioceptors, and then as rate-coding estimators operating at lower firing frequencies (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous afferents at the side of the mouth are also implicated in jaw movement. In particular, cutaneous mechanoreceptors at the oral angle have been shown to respond to passive jaw motion (26,27). Skin stretch at this location results in a compensatory reflex response that is normally evoked by unpredictable jaw position change (23).…”
Section: Speech Perception Testmentioning
confidence: 99%
“…Appenteng et al (1982) demonstrated that hair follicle receptors in rabbits show vigorous responses during chewing and concluded that these receptors may contribute the 'perception of jaw movement, but not jaw position'. The most likely explanation for this discrepancy is the marked difference in the density of hair follicles between human and rabbit skin.…”
Section: Hair Follicle Receptor Afferentsmentioning
confidence: 99%